2011
DOI: 10.1038/embor.2011.210
|View full text |Cite
|
Sign up to set email alerts
|

Dictyostelium chemotaxis: essential Ras activation and accessory signalling pathways for amplification

Abstract: Central to chemotaxis is the molecular mechanism by which cells exhibit directed movement in shallow gradients of a chemoattractant. We used Dictyostelium mutants to investigate the minimal requirements for chemotaxis, and identified a basal signalling module providing activation of Ras at the leading edge, which is sufficient for chemotaxis. The signalling enzymes PI3K, TorC2, PLA2 and sGC are not required for Ras activation and chemotaxis to folate or to steep gradients of cAMP, but they provide a memory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(112 citation statements)
references
References 29 publications
9
102
1
Order By: Relevance
“…Previous studies reported that disruption of four pathways (PI3K, TORC2, PLA 2 , and sGC) simultaneously abolishes chemotactic responses (10,11). In our hands, these cells were able to recruit LimE Δcoil following a brief pulse of flow, although the response was significantly reduced compared with cells lacking one (sGC) or two (sGC and PI3K) pathways (Fig.…”
Section: Role Of the Signal Transduction Network In The Response To Amentioning
confidence: 38%
“…Previous studies reported that disruption of four pathways (PI3K, TORC2, PLA 2 , and sGC) simultaneously abolishes chemotactic responses (10,11). In our hands, these cells were able to recruit LimE Δcoil following a brief pulse of flow, although the response was significantly reduced compared with cells lacking one (sGC) or two (sGC and PI3K) pathways (Fig.…”
Section: Role Of the Signal Transduction Network In The Response To Amentioning
confidence: 38%
“…Four signaling enzymes, PI3K, TorC2, PLA2 and sGC, have been implicated in chemotaxis (Chen et al, 2007;Kamimura et al, 2008;Liao et al, 2010;. Cells lacking all four enzyme activities show normal Ras activation in cAMP gradients, but can only exhibit chemotaxis in steep cAMP gradients (Kortholt et al, 2011). These observations suggest that symmetry breaking during chemotaxis occurs at the level of Ras activation, and that activation of downstream signaling pathways is not essential for Ras activation and chemotaxis.…”
Section: Introductionmentioning
confidence: 66%
“…In Dictyostelium, a shallow gradient of cAMP induces the activation of cAMP receptors and the associated heterotrimeric G-protein Ga2bc in a manner that is approximately proportional to the steepness of the gradient (Elzie et al, 2009;Jin et al, 2000;Xiao et al, 1997). In contrast, activation of Ras is much stronger in the front than in the rear of chemotaxing cells (Charest et al, 2010;Kortholt et al, 2011;Sasaki et al, 2004;Sasaki and Firtel, 2006;Zhang et al, 2008). Several studies have shown that inactivation of both rasC and rasG results in defective cAMP-mediated chemotaxis (Bolourani et al, 2006;Kortholt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the RasG activation was shown to occur independently of PI3K and actin polymerization, it has been proposed the presence of a positive feedback loop between RasG, PI3K and F-actin polymerization resulting in the amplification of the signal (Sasaki, A. et al 2004). The accumulation of PIP 3 serves as docking sites for many Pleckstrin homology (PH) domain-containing proteins, such as PKBA, that are important for cell polarity, cAMP relay and directional motility (Kae, H. et al 2004;Sasaki, A. et al 2006;Cai, H. and Devreotes, P. 2011;Kortholt, A. et al 2011). …”
Section: The Family Of Small Gtpases Ras Regulates Leading Edge Formamentioning
confidence: 99%